2014
DOI: 10.1182/blood.v124.21.411.411
|View full text |Cite
|
Sign up to set email alerts
|

ACE-536 Increases Hemoglobin and Reduces Transfusion Burden in Patients with Low or Intermediate-1 Risk Myelodysplastic Syndromes (MDS): Preliminary Results from a Phase 2 Study

Abstract: Introduction. ACE-536, a recombinant fusion protein containing modified activin receptor type IIB and IgG Fc, is being developed for the treatment of anemias due to ineffective erythropoiesis, such as myelodysplastic syndromes (MDS). Patients with MDS often have elevated levels of erythropoietin (EPO) and may be non-responsive or refractory to erythropoiesis-stimulating agents (ESAs). MDS patients have also been shown to have increased serum GDF11 levels (Suragani R et al., Nature Medicine 2014) and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…TI up to 30 to 40%, but in highly selected patient populations (31), (32) . Among innovative agents, the glutathione-Stransferase P1-1 (GSTP1-1) inhibitor Ezatiostat and the MAP kinase inhibitor ARRY 614 both gave a 29% erythroid response rate in heavily pretreated lower risk MDS without del5q (33), (34) , while early results using drugs with TGF beta pathway ligand traps (ACE 011 and ACE 536) appear promising (15), (35) .…”
Section: Toxicitymentioning
confidence: 99%
“…TI up to 30 to 40%, but in highly selected patient populations (31), (32) . Among innovative agents, the glutathione-Stransferase P1-1 (GSTP1-1) inhibitor Ezatiostat and the MAP kinase inhibitor ARRY 614 both gave a 29% erythroid response rate in heavily pretreated lower risk MDS without del5q (33), (34) , while early results using drugs with TGF beta pathway ligand traps (ACE 011 and ACE 536) appear promising (15), (35) .…”
Section: Toxicitymentioning
confidence: 99%
“…In fact, transforming growth factor‐β superfamily ligand inhibitors were recently found to correct ineffective erythropoiesis and promote late‐stage erythroid differentiation in mice (Dussiot et al , ; Suragani et al , ). Preliminary results from a phase II study investigating luspatercept (ACE‐536), a modified activin receptor IIB‐IgG Fc, in MDS patients with low or intermediate‐1 International Prognostic Scoring System (IPSS) risk not candidate or unresponsive/refractory to erythropoiesis stimulating agents, showed that 82% of patients achieved an erythroid haematological improvement according to International Working Group criteria (Cheson et al , ), with a significantly higher response rate in patients with ring sideroblasts and SF3B1 mutation (Platzbecker et al , ; Giagounidis et al , ). Based on this observation, a phase III multicentre randomized clinical trial is currently ongoing in IPSS‐R very low, low, or intermediate risk MDS with ring sideroblasts who require RBC transfusions (ClinicalTrials.gov Identifier: NCT02631070).…”
Section: Determinants Of Therapeutic Intervention and Treatment Optiomentioning
confidence: 99%
“…Currently, two clinical trials are recruiting patients to evaluate the effect of activin receptor type II ligand trap on anemia in patients diagnosed with low- or intermediate-1 risk MDS (ACE-011/sotatercept—NCT01736683; ACE-536/luspatercept—NCT01749514) and preliminary data suggest clinical activity. 115 …”
Section: Proposal Of ‘Osteohematology' As a Holistic Approach In Myelmentioning
confidence: 99%